Front Cover: Cooperative Ligands in Dissolution of Gold (Chem. Eur. J. 34/2021). Issue 34 (16th June 2021) - Heliövaara, Eeva; Liljeqvist, Henri; Muuronen, Mikko; Eronen, Aleksi; Moslova, Karina; Repo, Timo
Abstract : Dissolution of elemental gold occurs promptly with two different thiol ligands that act in a cooperative manner. The reaction benefits from the dynamic coordination sphere of Au I species that enables the dissolution to proceed via ligand‐exchange reactions. The dissolution proceeds from left to right and the birds represent the different Au species that form during the dissolution. Pyridine‐4‐thiol serves as the initiating ligand and 2‐mercaptobenzimidazole ligands stabilize the formed Au I cations in the dissolution. More information can be found in the Communication by T. Repo et al. (DOI: 10.1002/chem.202101028 ).